Characterization of RuO2–Rh2O3 supported on Ag1-xNbO3; at x=0, 0.1 and 0.5 for the H2 production. (1st March 2020) - Cruz-López, Arquímedes; Suárez-Vázquez, Santiago Iván; Solís-Casados, Dora Alicia; Ramos-Rivera, Carlos Alberto; Zanella, Rodolfo
Abstract: In this work, the characterization of the RuO2 –Rh2 O3 system supported on Ag1-x NbO3 (where x = 0, 0.1, and 0.5) prepared by the solid-state route at 900 °C for its employment as semiconductor in the production of hydrogen is presented. The physicochemical characterization evidences that the structural and electronic differences in the support were observed when the content of silver diminished by 50%. By X-ray diffraction of AgNbO3 stoichiometric ratio is confirmed, while the support, where there is a diminution of the silver content, evolved toward Ag2 Nb2 O11 mixed with the AgNbO3 with a band gap toward the visible region (2.5 eV). The results of scanning electron microscopy confirmed the presence of particles with sizes lower than 10 nm in both cases. Impregnation of the Ru–Rh bimetallic phase indicates that the amount of dispersed ruthenium compounds (RuO2, RuRh2 O4 and RuNbO4 ) were greater than the nominal charge (1.40 > RuO2 /Rh2 O3 <2.83). The electrochemical evaluation revealed a performance of 2.5-times greater for the 5%RuO2 -3% Rh2 O3 /Ag0.5 NbO3 with respect to its homologue: 5%RuO2 -3% Rh2 O3 /AgNbO3 .